Discovery of novel phthalimide analogs: Synthesis, antimicrobial and antitubercular screening with molecular docking studies - Rateb, Heba S. (EXCLI J, 2016)
In continuation of our endeavor towards the design and development of potent and effective antimicrobial agents, three series of phthalimide derivatives (4a-i, 5a-f, and 6a-c) were synthesized, fully characterized and evaluated for their potential antibacterial, antifungal and antimycobacterial activities. These efforts led to the discovery of nine compounds 4c, 4f, 4g, 4h, 4i, 5c, 5d, 5e, and 6c (MIC range from 0.49 to 31.5 μg/mL) with potent antibacterial, antifungal, and antimycobacterial activities. Ampicillin, ciprofloxacin, amphotericin B were used as references for antibacterial and antifungal screening respectively, while isoniazid was used as a reference for antimycobacterial testing. Furthermore, molecular modeling studies were done to explore the binding mode of the most active derivatives to M. tuberculosis enoyl reductase (InhA) and DNA gyrase B. Our study showed the importance of both hydrogen bonding and hydrophobic interactions as a key interaction with the target enzymes.